Optimalisasi manajemen strategi untuk meningkatkan loyalitas nasabah bsi - Zahira, Silvia Nazma (Maliki Interdisciplinary Journal, 2025)
This study highlights the importance of optimizing strategic management in enhancing customer loyalty at Bank Syariah Indonesia (BSI). With the intense competition in the Islamic banking industry, banks need to implement appropriate strategies to retain and improve customer loyalty. Various approaches, such as developing innovative products, improving service quality, and implementing digital technology, are utilized by BSI to meet customer expectations. This research aims to analyze the factors contributing to increased customer loyalty and how optimal management strategies can help create sustainable relationships between the bank and its customers. It is hoped that this study will provide deeper insights into effective strategies for building customer loyalty, particularly in the context of Islamic banking in Indonesia.